A new species of Neocaeculus (Acari: Prostigmata: Caeculidae) from Barrow island, Western Australia, with a checklist of world Caeculidae - Taylor, Christopher; Gunawardene, Nihara; Kinnear, A. (Universite de Montpellier III (Paul Valery), 2013)
Neocaeculus imperfectus new species is described from material collected on Barrow Island, Western Australia. Keys to genera and Australasian species of Caeculidae are provided, and the relationship between the genera Neocaeculus and Microcaeculus is discussed. A checklist of species for Caeculidae is provided.